Two-dimensional metal nanomaterials : synthesis, properties, and applications - Chen, Ye (2020)
As one unique group of two-dimensional (2D) nanomaterials, 2D metal nanomaterials have drawn increasing attention owing to their intriguing physiochemical properties and broad range of promising applications. In this Review, we briefly introduce the general synthetic strategies applied to 2D metal nanomaterials, followed by describing in detail the various synthetic methods classified in two categories, i.e. bottom-up methods and top-down methods. After introducing the unique physical and chemical properties of 2D metal nanomaterials, the potential applications of 2D metal nanomaterials in catalysis, surface enhanced Raman scattering, sensing, bioimaging, solar cells, and photothermal therapy are discussed in detail. Finally, the challenges and opportunities in this promising research area are proposed.